Krill oil ameliorates benign prostatic hyperplasia by regulating G1-phase cell cycle arrest and altering signaling pathways and benign prostatic hyperplasia-associated markers - Hoon Kim; Jongyeob Kim; Byungdoo Hwang; SangYong Park; Ji-Yeon Shin; EunByeol Go; Jae Sil Kim; Youngjin Roh; SoonChul Myung; Seok-Joong Yun; YungHyun Choi; Wun-Jae Kim; et al. (Food Science and Human Wellness, 2024)
Krill oil (KO) exhibits various biological activities, such as anti-inflammatory and antitumor effects. However, the inhibitory effects of benign prostatic hyperplasia (BPH) in vitro and in vivo have not yet been studied. This study investigated the anti-BPH effects of KO extracted by an enzymatic hydrolysis method. KO treatment inhibited the proliferation of WMPY-1 and BPH-1 cells by induction of G0/G1 phase arrest through the modulation of positive and negative regulators in both prostate cell types. KO treatment stimulated phosphorylation of c-Jun N-terminal kinase (JNK) and p38 signaling. In addition, KO changed the expression of BPH-related markers (5α-reductase, androgen receptor, FGF, Bcl-2, and Bax) and the activity of the proliferation-mediated NF-κB binding motif. KO-induced levels of proliferation-mediated molecules of prostate cells were attenuated in the presence of siRNA-specific p-38 (si-p38) and JNK (si-JNK). Furthermore, the administration of KO alleviated prostate size and weight and the cell layer thickness of prostate glands in a testosterone enanthate-induced BPH rat model. KO treatment altered the level of dihydrotestosterone in serum and the expression levels of BPH-related markers in prostate tissues. Finally, KO-mediated inhibition of prostatic growth was validated by histological analysis. These results suggest that KO has an inhibitory effect on BPH in prostate cells in vitro and in vivo. Thus, KO might be a potential prophylactic or therapeutic agent for patients with BPH.